A.
P(x) = 2x^2 + 74x + 644
B.
P(x) = 2x^2 + 28x - 414
C.
P(x) = 2x^2 + 102x + 1,288
D.
P(x) = 2x^2 + 110x + 1,472
Answer:
It's B.
Step-by-step explanation:
First is x + 23 and second is 2x - 18.
So the product is
(x + 23)(2x - 18)
= 2x^2 - 18x + 46x - 414
= 2x^2 + 28x - 414
The length of longer leg is 24 feet, shorter leg is 18 feet and hypotenuse is 30 feet.
Step-by-step explanation:
Let,
Longer leg = a = x
Shorter leg = b = x - 6
Hypotenuse = c = x + 6
As the triangle is right angles, therefore, using pythagoras theorem;
Adding (-x² - 12x-36) on both sides
Taking x common;
Either,
x=0
or,
x-24 = 0 => x=24
As length cannot be 0 therefore,
Longer leg = x = 24 feet
Shorter leg = x-6 = 24-6 = 18 feet
Hypotenuse = x+6 = 24+6 = 30 feet.
The length of longer leg is 24 feet, shorter leg is 18 feet and hypotenuse is 30 feet.
Keywords: triangle, addition
Learn more about triangles at:
#LearnwithBrainly
B). Subtract 1.3 from both sides of the equation, subtract 4.6x to both sides of the equation, then divide by the coefficient of x.
C). Add 1.3 to both sides of the equation, subtract 4.6x to both sides of the equation, then divide by the coefficient of x.
D). Add 1.3 to both sides of the equation, subtract 4x to both sides of the equation, then divide by the coefficient of x.
The correct steps to solve the expression will be;
''Add 1.3 to both sides of the equation, subtract 4x to both sides of the equation, then divide by the coefficient of x.''
Option D is true.
What is an expression?
Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
The expression is,
⇒ -1.3 + 4.6x = 0.3 + 4x
Now,
Solve the expression as;
⇒ -1.3 + 4.6x = 0.3 + 4x
Add 1.3 both side, we get;
⇒ -1.3 + 4.6x + 1.3 = 0.3 + 4x + 1.3
⇒ 4.6x = 1.6 + 4x
Subtract 4x both side,
⇒ 4.6x - 4x = 1.6 + 4x - 4x
⇒ 0.6x = 1.6
Divide by 0.6,
⇒ x = 2.67
Thus, The correct steps to solve the expression will be;
''Add 1.3 to both sides of the equation, subtract 4x to both sides of the equation, then divide by the coefficient of x.''
Option D is true.
Learn more about the mathematical expression visit:
#SPJ5
Write the equation of line m.
Write the equation of line n.
Line m equation is .
Line n equation is .
Step-by-step explanation:
Here , we have Line m has no y-intercept, and its x-intercept is (-5, 0). Line n has no x-intercept, and its y-intercept is (0, 3). Let's find out equation of both line step by step:
Equation of line m:
Line m has no y-intercept , that means line is never intersecting y-axis which is only possible when line is parallel to y-axis , also this line have x-intercept as (-5,0) i.e. cuts x-axis at x = -5 .
⇒
⇒
∴ Line m equation is .
Equation of line n:
Line n has no x-intercept , that means line is never intersecting x-axis which is only possible when line is parallel to x-axis , also this line have y-intercept as (0,3) i.e. cuts y-axis at y = 3 .
⇒
⇒
∴ Line n equation is .